Relationship between the cognitive load and the learning success in applying force diagrams: eye-tracking study - Omarbakiyeva, Yultuz; Hahn, Larissa; Klein, Pascal; Krumphals, Ingrid; Watzka, Bianca (Frontiers in Education, 2025)
IntroductionThis paper is concerned with investigating the cognitive demands of solving force diagram tasks in different scenarios, specifically in the wind context.MethodsIn this study, students were trained using worked examples and then completed tasks in two different scenarios while their eye movements were monitored with eye-tracking technology. After completing the tasks, cognitive load was assessed to evaluate the impact of task complexity on cognitive processing. Eye-tracking metrics were analyzed in detail to identify gaze strategies, differences and similarities.ResultsIt was found that a three-force scenario (surface wind formation) induced a higher intrinsic cognitive load than a two-force scenario, which is not only theoretically justified by cognitive load theory, but also confirmed by eye-tracking metrics. Although correlation analyses show no significant relationship between the ability to mentally rotate and learning success, the role of mental rotation in problem solving is highlighted by eye-tracking data.DiscussionOur results contribute to a better understanding of the learning and problem-solving mechanisms involved in wind direction determination and offer possible implications for the design of more effective teaching and learning methods in this area.